A phase III randomised, double-blind, parallel-group study comparing SB4 with etanercept reference product in patients with active rheumatoid arthritis despite methotrexate therapy. Issue 1 (6th July 2015) - Emery, Paul; Vencovský, Jiří; Sylwestrzak, Anna; Leszczyński, Piotr; Porawska, Wieslawa; Baranauskaite, Asta; Tseluyko, Vira; Zhdan, Vyacheslav M; Stasiuk, Barbara; Milasiene, Roma; Barrera Rodriguez, Aaron Alejandro; Cheong, Soo Yeon; et al.
Abstract : Objectives: To compare the efficacy and safety of SB4 (an etanercept biosimilar) with reference product etanercept (ETN) in patients with moderate to severe rheumatoid arthritis (RA) despite methotrexate (MTX) therapy. Methods: This is a phase III, randomised, double-blind, parallel-group, multicentre study with a 24-week primary endpoint. Patients with moderate to severe RA despite MTX treatment were randomised to receive weekly dose of 50 mg of subcutaneous SB4 or ETN. The primary endpoint was the American College of Rheumatology 20% (ACR20) response at week 24. Other efficacy endpoints as well as safety, immunogenicity and pharmacokinetic parameters were also measured. Results: 596 patients were randomised to either SB4 (N=299) or ETN (N=297). The ACR20 response rate at week 24 in the per-protocol set was 78.1% for SB4 and 80.3% for ETN. The 95% CI of the adjusted treatment difference was −9.41% to 4.98%, which is completely contained within the predefined equivalence margin of −15% to 15%, indicating therapeutic equivalence between SB4 and ETN. Other efficacy endpoints and pharmacokinetic endpoints were comparable. The incidence of treatment-emergent adverse events was comparable (55.2% vs 58.2%), and the incidence of antidrug antibody development up to week 24 was lower in SB4 compared with ETN (0.7% vs 13.1%). Conclusions: SB4 was shown to be equivalent with ETN in terms of efficacy at week 24. SB4 was well tolerated with a lower immunogenicity profile. The safety profile of SB4 was comparable with that of ETN. Trial registration numbers: NCT01895309, EudraCT 2012-005026-30.